ANALISIS PENGETAHUAN WAJIB PAJAK TENTANG PERATURAN MENTERI KEUANGAN NOMOR 91 TAHUN 2015 DI KPP PRATAMA PEKANBARU TAMPAN - Kurniadi, Romi; Syahza, Almasdi; ', RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This reaserch aimed to analyze the knowledge taxpayers on Finance Minister Regulation No. 91 in 2015 in KPP Pekanbaru Tampan. The research was conducted in Pekanbaru. This type of research is descriptive quantitative research with sample of 100 taxpayers from 127. 172 population. Data obtained from the administration of the questionnaire in the form of test, and then analyzed by categorizing the average results of tests in three categories: low, medium, and high. The results show the average results of tests on the indicator legal basis was 0.52 (medium), indicator of the type of sanctions that can be forgive was 2.23 (moderate), the indicator of term was 1.56 (medium) and billing indicator 8.1 (medium). So overall the results showed that taxpayers knowledgeis not good enough.Keywords: knowledge, compliance, taxpayer